JENIS-JENIS PAKU EPIFIT DAN TUMBUHAN INANGNYA DI TAHURA RONGGO SOERYO CANGAR - Romaidi, Romaidi; Solikha, Maratus; Minarno, Eko Budi (El-Hayah : Jurnal Biologi, 2012)
A study to know kinds of epiphytic ferns and their host plants has been conducted in Forest Park Ronggo Soeryo Cangar (FPRSC). The method used to inventory kind of ferns and their host plants is cruising method on some defined areas. These areas include (1) the back of the tourist hot Tahura R. Soejo Cangar, (2) the forest area behind the inn of FPRSC and (3) forest areas that are included in the slopes of Mount Arjuna. Once the sample is collected then be identified in the Taxonomy Laboratory, Department of Biology, Faculty of Science and Technology, UIN Maliki Malang. The results showed that there were 12 species of epiphytic ferns type has been found and 19 of its host tree and plant species are generally included in the staging tree.